Analisis Kondisi Keuangan Pemerintah Daerah Berdasarkan Model Sistem Pemantauan Tren Keuangan (SPTK) - Ni Komang Sri Laksmiwati; Ivan Yudianto (Jurnal Riset Akuntansi, 2023)
Local Government Financial Statements (LKPD) are made as a form of accountability and transparency in the implementation of government activities. From the figures in the LKPD, analyses can be carried out related to the financial condition of the region. The purpose of this study is to provide an overview of the financial condition and financial trends of the Badung Regency Government in 2018-2022 based on the Financial Trend Monitoring System (FTMS) model which consists of 3 dimensions and 15 indicators. This research is a descriptive analysis conducted by descriptive statistical analysis based on secondary data in the form of LHP on LKPD Badung Regency 2018-2022 and interviews to confirm the cause of the decline in the financial trend of an indicator. The results of this study are as many as 11 of the 15 existing indicators experienced a positive (good) trend for 5 (five) years including the Operating Income indicator, PAD per Expenditure Ratio, Government Cash Ratio, Cash and Receivables Ratio, Current Asset Ratio, Short-Term Debt, Long-Term Debt, Revenue per Debt, Financial Balance, Financial Flexibility, and Infrastructure Maintenance. Meanwhile, the other 4 indicators experienced a negative trend (not good) consisting of indicators of Revenue per Personnel Expenditure, Independence Ratio, Intergovernmental Ratio, and Income per Capita.